2017
DOI: 10.21577/1984-6835.20170091
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Analysis of Essential Oil and Hydrolates of Leaves, Inflorescences and Stems of Piper chimonanthifolium Kunth

Abstract: Resumo: Plantas do gênero Piper são frequentemente utilizadas comercialmente. A espécie Piper chimonanthifolium Kunth. apresenta poucos estudos em literatura quanto a sua composição química e atividades biológicas. Óleos essenciais de outras espécies deste gênero apresentam boas atividades biológicas, principalmente contra microrganismos. Este trabalho apresenta uma comparação da composição química de óleos essenciais e hidrolatos de folhas, inflorescências e caules desta espécie. As amostras foram obtidas por… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 19 publications
(17 reference statements)
0
9
0
Order By: Relevance
“…According to Riani et al [38], the presence of piperitone in the chemical constitution of a species can make it toxic. In the same way, supporting the results obtained in this study, since the present chemical constituent is one of the main identified compounds of the species of study.…”
Section: Discussionmentioning
confidence: 99%
“…According to Riani et al [38], the presence of piperitone in the chemical constitution of a species can make it toxic. In the same way, supporting the results obtained in this study, since the present chemical constituent is one of the main identified compounds of the species of study.…”
Section: Discussionmentioning
confidence: 99%
“…Piperitone was found in all samples of P. chimonanthifolium. This monoterpene is the major compound in all hydrolates and in the essential oils of the stem and leaf, and the second most abundant compound in the essential oil of inflorescence [35]. In case of C. subhirtella and C. serrulata benzaldehyde was the key component of the essential oils, while benzaldehyde, as well as mandelonitrile was the principal compound of hydrolates [19].…”
Section: Introductionmentioning
confidence: 99%
“…The extracts were analyzed from electron impact ionization mass spectrometry (EI-MS) at 70eV, and the compounds were identified in scan mode with positive polarity of ions 20-300 m/z with a time of 250.0 ms. All the essential oils were injected with a volume of 1 µL, using a split ratio of 1:350 for C. ladanifer and T. capitata, and 1:100 for H. italicum, which was previously diluted with an organic solvent. Regarding the hydrolates of H. italicum, O. basilicum and T. capitata, they were subjected to a liquid-liquid extraction (LLE) with an organic solvent (hexane) (Collin and Gagnon, 2016;Riani et al, 2017). The aqueous phase was separated from the organic phase, and the organic phase was injected and analyzed using the same chromatographic method as essential oils.…”
Section: Essential Oils and Hydrolates Analysis By Gc-msmentioning
confidence: 99%
“…The requested information has been added to the text. Ln 177: "Regarding the hydrolates of H. italicum, O. basilicum and T. capitata, they were subjected to a liquid-liquid extraction (LLE) with an organic solvent (hexane) (Collin and Gagnon, 2016;Riani et al, 2017). The aqueous phase was separated from the organic phase, and the organic phase was injected and analyzed using the same chromatographic method as essential oils.…”
mentioning
confidence: 99%